2020
DOI: 10.1136/bjsports-2020-102823
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and incidence of injuries in para athletes: a systematic review with meta-analysis and GRADE recommendations

Abstract: ObjectiveTo investigate prevalence, incidence and profile of musculoskeletal injuries in para athletes.DesignSystematic review.Data sourcesSearches were conducted in MEDLINE, EMBASE, AMED, SPORTSDiscus, CINAHL and hand searching.Eligibility criteriaStudies were considered if they reported prevalence or incidence of musculoskeletal injuries in para athletes. Study selection, data extraction and analysis followed the protocol. Meta-analyses were conducted to estimate the prevalence and incidence rate among studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 68 publications
1
16
0
1
Order By: Relevance
“…The prevalence of urolithiasis was found to be affected by the sample size in this meta-analysis. The larger the screening scale, the lower the prevalence of urolithiasis, which is consistent with screening for many diseases [73]. We suggest that this appearance might be related to small sample studies can achieve refined project management [74] and researchers are more willing to focus on a positive result.…”
Section: Discussionsupporting
confidence: 57%
“…The prevalence of urolithiasis was found to be affected by the sample size in this meta-analysis. The larger the screening scale, the lower the prevalence of urolithiasis, which is consistent with screening for many diseases [73]. We suggest that this appearance might be related to small sample studies can achieve refined project management [74] and researchers are more willing to focus on a positive result.…”
Section: Discussionsupporting
confidence: 57%
“…Injuries not only pose a limitation on sports performance, but also an additional barrier to activities of daily living for athletes depending on a wheelchair or crutches for mobility. 21 Shoulder, trunk and back injury prevention is of outmost importance and should be implemented in regular training for all athletes with high loads on the upper body. 53,54 Our suggestion for injury prevention training for Para athletes are the freely available resources with the Get Set -Train Smarter application and www.fittoplay.org.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…1,2 A recent systematic review on the risk of musculoskeletal injuries among Para athletes revealed that the quality of the available evidence is low, and called for larger sample sizes and better quality studies. 21 Longitudinal data will facilitate a more comprehensive understanding of illness and injury patterns overall, enabling better planning of year-round medical services for Para athletes, 22,23 and informing initiatives to protect athlete health.…”
Section: Introductionmentioning
confidence: 99%
“…Each term would be rated as low risk, high risk, and unclear. The Grading of Recommendations Assessment, Development, and Evaluation System (GRADE) ( 32 ) would be used to grade the quality of the evidence for main outcomes, and the quality of the evidence was rated as high, moderate, low, or very low according to the GRADE grading scale. The evaluation was conducted independently by two reviewers (Zhao-bo Yan and Zhi-miao MuRong); any disagreements would be resolved by a third reviewer (Mai-lan Liu).…”
Section: Methodsmentioning
confidence: 99%